Behavior of precast concrete beam and slab elements under service conditions using LISA FEA - Wahyudi Efendi, Aco (SAINSTECH NUSANTARA, 2024)
Development has increased massively after the announcement of the IKN area in the area, one of which is the construction of a jetty to accommodate logistics for construction work from infrastructure and facilities to support road, bridge and building construction activities in the IKN area. In this research, we explore how to construct the IKN dock in a timely manner so that it may be utilized appropriately. Researchers perform an examination of the behavior of precast beams and jetty floor slab to acquire stress values and deformations that occur in the process of working methods when installed, casting implementation, and dock service circumstances when using this precast technique. The usage of precast is analyzed utilizing micro software analysis of the finite element technique, namely LISA FEA V.8, to create stress hues behavior that happens. From the results of the modeling simulation above, it can be seen that the largest dominant stress distribution occurs on the side of the beam ear meeting with the deck slab/half slab, the stress occurs according to the working method step between 1.774 MPa in the condition of the slab being installed and increases when the implementation of wet concrete casting becomes 2.567 MPa and when the service condition, the stress again increases to 9,258 MPa.